Analysis of the Development Needs of PMRI-Based Pop-Up Book Geometry Media on Cube Materials - Ariyani, Pipit; Putri, Ratu Ilma; Somakim, Somakim (Papanda Publisher, 2025)
Understanding the concept of the cube remains a challenge for elementary school students due to the lack of concrete and contextual learning materials. Abstract learning makes it difficult for students to understand the shape and nature of building spaces. This study aims to analyse the need for developing geometry learning media in the form of pop-up books based on Indonesian Realistic Mathematics Education (PMRI) using cube materials in grade 2 elementary school. The research method used is Design Research. Data collection was conducted through interviews with three mathematics teachers and twenty-four second-grade students of SDN 1 Air Balui in Musi Banyuasin Regency. The analysis of student needs employs closed interviews. In contrast, the analysis of teacher needs utilises semi-structured interviews to gather more in-depth information about the needs and expectations of geometry learning media among grade II students. Data were analysed using qualitative descriptive analysis, employing the Miles and Huberman analysis approach through three stages: data reduction, data presentation, and conclusion. The results show that teachers and students have a high need for visual, manipulative, and integrated learning media to explain the properties of cubes. The percentage analysis indicates very high scores in pedagogical (90–94%), technical (85%), aesthetic (92%), and evaluation aspects (88–90%), while cognitive aspects (77–79%) are categorised as high. These findings suggest that PMRI-based pop-up books have the potential to enhance students' Understanding of concepts by connecting abstract geometric concepts to concrete experiences. The results of this needs analysis are the basis for the development and validation stage of contextual, engaging, and practical geometry learning media for basic education.